Nutrición parenteral: la prisión que permite sobrevivir ante una condición de insuficiencia intestinal. - María Osorio-Cock, Lina; Giraldo-Villa, Adriana; Marcela López-Gómez, Lina; Alejandra Pérez-Ricci, Ximena; Yepes-Delgado, Carlos Enrique (Revista Colombiana de Gastroenterología)
Objective: Intestinal failure refers to a reduction in intestinal function that necessitates intravenous supplementation of macronutrients, water, or electrolytes due to the intestine's inability to absorb these substances adequately to maintain health and growth. This study aims to explore the experiences and challenges faced by patients enrolled in the intestinal rehabilitation program at Hospital Pablo Tobón Uribe in Medellín. Methodology: This qualitative study adopts a hermeneutic approach and utilizes grounded theory techniques. The sampling process involved both selective and theoretical sampling. A total of 20 semi-structured interviews were conducted, with eight interviews including contributions from family members. The data analysis commenced with open coding, followed by the grouping of codes into descriptive categories. Dimensions and properties were identified within these categories, and analytical categories were subsequently developed through axial and selective coding. This iterative process led to the emergence of the final paradigm matrix. Results: The study revealed that the healthcare system inadequately addresses the needs and expectations of patients with intestinal failure, leading to increased uncertainty about the disease's origin and future prognosis. Intestinal failure and its treatment disrupt various aspects of patients' lives, including personal, family, and work domains. Social stigmatization and rejection are prominent, underscoring the importance of support from family and close individuals in facilitating adaptation and revaluing life. Conclusions: Coping with the challenges of intestinal failure entails embracing the necessity of relying on parenteral nutrition, which is perceived as a prison that paradoxically enables survival.